2016
DOI: 10.1002/anie.201602604
|View full text |Cite
|
Sign up to set email alerts
|

UV/Vis Action Spectroscopy and Structures of Tyrosine Peptide Cation Radicals in the Gas Phase

Abstract: We report the first application of UV/Vis photodissociation action spectroscopy for the structure elucidation of tyrosine peptide cation radicals produced by oxidative intramolecular electron transfer in gas-phase metal complexes. Oxidation of Tyr-Ala-Ala-Ala-Arg (YAAAR) produces Tyr-O radicals by combined electron and proton transfer involving the phenol and carboxyl groups. Oxidation of Ala-Ala-Ala-Tyr-Arg (AAAYR) produces a mixture of cation radicals involving electron abstraction from the Tyr phenol ring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Based on the analysis of peptide radical chromophores [58] +• are most straightforward in that they both result in a dominant loss of the Tyr side chain. This is consistent with the Tyr-O radical structure of this ion where loss of C 7 H 6 O is the lowest energy process in CID and the Tyr-O radical is the absorbing chromophore for UVPD [43]. We cannot distinguish whether UVPD occurs from an excited electronic state or after vibronic transition to a vibrationally hot ground electronic state because both are expected to display similar reactivity.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Based on the analysis of peptide radical chromophores [58] +• are most straightforward in that they both result in a dominant loss of the Tyr side chain. This is consistent with the Tyr-O radical structure of this ion where loss of C 7 H 6 O is the lowest energy process in CID and the Tyr-O radical is the absorbing chromophore for UVPD [43]. We cannot distinguish whether UVPD occurs from an excited electronic state or after vibronic transition to a vibrationally hot ground electronic state because both are expected to display similar reactivity.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast, the loss of H does not have an analogy in CID and is likely proceeding from an excited electronic state of the ion. A previous UV photodissociation action spectroscopy study has concluded that [AAAYR] +• was a mixture of isomeric radicals [43], and thus it is possible that the observed photodissociations originated from different radical isomers.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Whereas UV photo-excitation (UVPD) at 193 nm results in nonspecific dissociation of many bonds in ETD fragment ions, UVPD at 355 nm has been shown to trigger backbone and side-chain bond cleavage that were specific for amino acid residues in the peptide ion [22][23][24][25][26]. When combined with action spectroscopy [9], UV-VIS photodissociation provides information on mass-resolved photodissociation channels pertinent to different excited electronic states of the ion [27,28].…”
Section: Introductionmentioning
confidence: 99%